2019
DOI: 10.1055/a-0732-487
|View full text |Cite
|
Sign up to set email alerts
|

Management of colorectal laterally spreading tumors: a systematic review and meta-analysis

Abstract: Objective and study aims  To evaluate the efficacy and safety of different endoscopic resection techniques for laterally spreading colorectal tumors (LST). Methods  Relevant studies were identified in three electronic databases (PubMed, ISI and Cochrane Central Register). We considered all clinical studies in which colorectal LST were treated with endoscopic resection (endoscopic mucosal resection [EMR] and/or endoscopic submucosal dissection [ESD]) and/or transanal minimally invasive surgery (TEMS). Rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 72 publications
4
65
0
1
Order By: Relevance
“…Furthermore, although multiple published studies cite early adenoma recurrence rates, data for very late recurrence rates at 24 months after ER are limited. 3,4 In the present study, multivariate analysis found that the risk factors for early recurrence at 3 to 6 months were piecemeal resection, adjunctive use of argon plasma coagulation, and lesions occupying 75% of the luminal circumference. However, multivariate analysis derived risk factors for very late recurrence detected at >12 to 18 months (ie, at 24 months) were lesions >60 mm and piecemeal resection.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…Furthermore, although multiple published studies cite early adenoma recurrence rates, data for very late recurrence rates at 24 months after ER are limited. 3,4 In the present study, multivariate analysis found that the risk factors for early recurrence at 3 to 6 months were piecemeal resection, adjunctive use of argon plasma coagulation, and lesions occupying 75% of the luminal circumference. However, multivariate analysis derived risk factors for very late recurrence detected at >12 to 18 months (ie, at 24 months) were lesions >60 mm and piecemeal resection.…”
supporting
confidence: 46%
“…2 These results are consistent with some of the recurrence risk factors that have been identified in previous studies. [3][4][5][6][7] In the present study, only 1 patient experienced an invasive cancer within a recurrent lesion. However, this patient's surveillance and treatment had significant delays because of confounding medical problems.…”
mentioning
confidence: 95%
“…Although focused literature assessing surgical and transanal endoscopic microsurgery (TEM) management in colorectal LST has not been well documented, there is conventional perception amongst surgeons that these remain the most reliable modalities of treatment in achieving curative resection and lowering risks of future recurrence; however, the adverse event (AE) rate very substantially exceeds that of endoscopic therapy for laparoscopic or open resectional surgery with a 30-day mortality at 0.7 % and major postoperative complication rates of 14 % 4 . In this edition of Endoscopy International Open, Russo et al present a systematic review and meta-analysis comparing endoscopic management options for colorectal LST 5 . LST originally managed via endoscopy required eventual surgery in 2.7 % of cases either due to AEs (pooled rate 0.5 %), recurrences in follow-up (pooled rate 0.5 %) or incomplete/non-curative resection (pooled rate 4.3 %) 5 .…”
Section: Surgery Vs Endoscopymentioning
confidence: 99%
“…In this edition of Endoscopy International Open, Russo et al present a systematic review and meta-analysis comparing endoscopic management options for colorectal LST 5 . LST originally managed via endoscopy required eventual surgery in 2.7 % of cases either due to AEs (pooled rate 0.5 %), recurrences in follow-up (pooled rate 0.5 %) or incomplete/non-curative resection (pooled rate 4.3 %) 5 . The continued widespread use of major surgery as the popular choice in benign polyp management has recently been questioned in an editorial by Prof. Douglas Rex in Endoscopy, exploring the reluctance of both endoscopists and surgeons to move to endoscopic approaches for both patient and health economic benefits 6 .…”
Section: Surgery Vs Endoscopymentioning
confidence: 99%
“…Large (≥ 20 mm) polyps (LPs) are increasingly detected in FOBT-enriched colonoscopies, malignant in a non-negligible proportion of cases and challenging to remove endoscopically. Several guidelines have been recently published on colorectal polypectomy and management of LPs (3)(4)(5)(6) along with systematic reviews and metaanalyzes (7)(8)(9). Some authors claim that all benign colorectal polyps can be removed by endoscopic resection (ER), using endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD) or hybrid techniques.…”
Section: Introductionmentioning
confidence: 99%